Technology choice and price signaling in markets for label credence goods - Martin Obradovits; Markus Walzl (Johannes Kepler University of Linz, Department of Economics, 2025)
Consumers increasingly value the environmental and social responsibility of the production processes used by firms, yet these processes often remain unobservable, even after consumption. In this paper, we develop a simple model to examine firms' technology choices and subsequent price competition in markets for such label credence goods with hidden process attributes. Using a multi-sender signaling framework, we show that in the payoff-dominant equilibrium, firms can partially signal their production choices and avoid Bertrand competition when at least one firm adopts a green technology. Surprisingly, increasing consumers' environmental concern or eliminating the information asymmetry may reduce social welfare by discouraging green production.
Keywords: D82; D83; L13; L15; 330; label credence goods; technology choice; asymmetric information; price competition; signaling; green production